PEMBERIAN BEBERAPA DOSIS TRICHO-KOMPOS LEGUMINOSA TERFORMULASI TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Very Fernando H; Fifi Puspita; Hafiz Fauzana (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research was purposed to study the effect and get the best dosage of formulated leguminose Tricho-compost on cocoa seedlings (Theobroma cacao L.). The research was conducted by Completely Randomized Design (CRD) that consists of 5 treatment and 4 repelication, ex formulated leguminose Tricho-compost dosage 0 g/polybag, 25 g/polybag, 50 g/polybag, 75 g/polybag and 100 g/polybag. The parameters observed were seed height, leaf number, stem diameter, leaf area, wet weight, root volume, root shoots ratio and dry weight of seedlings. The results of research showed that the giving of formulated leguminose tricho-compost of 75 g/polybags was the best dosage that could increase the height of seedlings, leaf number, stem diameter, leaf area, wet weight, root volume, root shoots ratio and dry weight of cocoa seedlings.Keywords: cocoa, leguminose, tricho-compost, formulated